Business as Plan B: Institutional Foundations of Gender Inequality in Entrepreneurship across 24 Industrialized Countries - Thébaud, Sarah (Administrative science quarterly, 2015)
This article develops and empirically evaluates an institutional theory of gender inequalities in business start-up, ownership, and growth orientation. I argue that in contexts in which institutional arrangements such as paid leave, subsidized childcare, and part-time employment opportunities mitigate work-family conflict, women are less likely to opt for business ownership as a fallback employment strategy. As a result, women in these contexts may be relatively less well represented among entrepreneurs as a whole but more well represented in growth-oriented forms of entrepreneurship. To evaluate this claim, I analyze survey data from 24 countries over the span of eight years. Multilevel analyses show that supportive work–family institutions are associated with larger gender gaps in the odds of early-stage and established business ownership but smaller gender gaps among business owners in terms of their business size, growth aspirations, and propensity to innovate or use new technology. Consistent with my theoretical argument, women business owners are also less likely to report pursuing entrepreneurship because they lacked attractive employment options in contexts in which supportive institutions are in place. Findings suggest that institutional contexts characterized by salient work–family conflict may fuel women's aggregate representation in business activity but reinforce their segregation into less growth-oriented (and thus lower-status) ventures.